PENGUATAN KEWENANGAN BAWASLU: URGENSI PENYIDIKAN TINDAK PIDANA PEMILU DEMI KEADILAN, EFEKTIVITAS DAN INTEGRITAS DEMOKRASI - Nico rahman; Khofi Khofi; Fadiyatul Hadiyah (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2025)
The enforcement of electoral laws is a critical element in safeguarding the integrity and legitimacy of democracy in Indonesia. The Election Supervisory Agency (Bawaslu), as the oversight body, plays a central role in ensuring elections are conducted honestly, fairly, and with dignity. However, Bawaslu’s limited authority, confined to issuing recommendations without investigative powers, results in low effectiveness in electoral law enforcement. Coordination through the Integrated Law Enforcement Center (Gakkumdu) is often hindered by bureaucratic complexities, differing interpretations of authority, and tight deadlines, causing many violation cases to stall before reaching the investigation stage. This article examines Bawaslu’s structural weaknesses from juridical perspectives, national case studies, and international comparisons with electoral law enforcement systems in the Philippines, Brazil, and South Africa. The analysis demonstrates that granting Bawaslu limited investigative authority can strengthen electoral justice, expedite legal processes, and enhance public trust in democracy. Institutional reforms integrating oversight, inquiry, and investigative functions are proposed as a solution to achieve effective, independent, and integrity-driven electoral law enforcement, in line with the principles of the rule of law and social justice. Keywords: Electoral law enforcement, Bawaslu, electoral justice, investigative authority